Addressing childhood blindness: A collective responsibility - Muhammad Ajmal Chaudhary (Journal of the Pakistan Medical Association, 2025)
Childhood blindness remains a significant public healthconcern1 in Pakistan, placing a substantial economicburden2,3 on families and the wider community. TheNational Committee for the Prevention of Blindnessrecently revealed a sobering statistic: approximately onepercent of the Pakistani population lives in darkness, withan estimated 1.2 per 1,000 children affected. Alarmingly,at least one-third of these cases are preventable. Whilethe World Health Organization (WHO) and theInternational Agency for the Prevention of Blindness(IAPB) have launched global initiatives to eliminateavoidable blindness, childhood blindness being a prioritybut the real challenge lies in translating thesecommitments into concrete action at the national andcommunity levels. Continue...